ANALYSIS OF SOLID WASTE MANAGEMENT STRATEGY IN PELAYANGAN DISTRICT, JAMBI CITY, INDONESIA - Murfid Falih Setyonegoro; Rita Retnowati; Sri Wahyuni (Journal of Science Innovare, 2022)
The length of the title is recommended to not exceed twenty words. The abstract should be clear, concise, and descriptive. This abstract should provide a brief introduction to the problem, and objective of the paper, followed by a statement regarding the methodology and a summary of the results. The abstract should end with a comment on the significance of the results or a brief conclusion. Acronyms and citations are discouraged in the abstract. The abstract should not exceed 200 words and be followed by keywords (not more than 5 words or phrases arranged in alphabetical order). Keywords are covering scientific and local names (if any), research themes, and special methods used; and sorted from A to Z. The length of the title is recommended to not exceed fifteen words. The abstract should be clear, concise, and descriptive. This abstract should provide a brief introduction to the problem, and objective of the paper, followed by a statement regarding the methodology and a summary of the results. The abstract should end with a comment on the significance of the results or a brief conclusion. Acronyms and citations are discouraged in the abstract. The abstract should not exceed 200 words and be followed by keywords.